Pharmacodynamic monitoring of cyclosporine A by NFAT-regulated gene expression and the relationship with infectious complications in pediatric renal transplant recipients - Billing, Heiko; Giese, Thomas; Sommerer, Claudia; Zeier, Martin; Feneberg, Reinhard; Meuer, Stefan; Tönshoff, Burkhard (Pediatric transplantation, 2010)
Billing H, Giese T, Sommerer C, Zeier M, Feneberg R, Meuer S, Tönshoff B. Pharmacodynamic monitoring of cyclosporine A by NFAT-regulated gene expression and the relationship with infectious complications in pediatric renal transplant recipients. Pediatr Transplantation 2010: 14:844-851. © 2010 John Wiley & Sons A/S. Abstract: Pharmacokinetic monitoring of CsA is unsatisfactory, because at comparable CsA blood concentrations, the frequency and severity of adverse effects vary considerably among patients. We have therefore recently developed a precise, reliable, and robust whole-blood pharmacodynamic assay that measures the suppression of CsA-target genes in T lymphocytes. Because of the different characteristics of CsA pharmacokinetics in children and the higher propensity for infectious complications, this assay requires validation in the pediatric patient population. We therefore quantified in a prospective study of 45 pediatric renal transplant recipients the residual expression of NFAT-regulated genes in lymphocytes by RT-PCR and correlated these findings with the frequency of recurrent infections in the maintenance period post-transplant. Patients with recurrent infections showed a significantly stronger inhibition of NFAT-regulated gene expression (18.2%) than patients without recurrent infections (31.7%; p = 0.012). This difference was specific, because various PK parameters of CsA and the concomitant immunosuppressive therapy were comparable between patients. Multivariate regression analysis showed that patient age and residual NFAT-regulated gene expression were the only independent determinants of recurrent infections. By ROC curve analysis, a cutoff value of 23% residual NFAT-regulated gene expression had the highest sensitivity (71.1%) and specificity (65.4%) for the discrimination of patients with and without recurrent infections. Pharmacodynamic monitoring of CsA by measurement of residual NFAT-regulated gene expression in T lymphocytes has the potential to identify over-immunosuppressed pediatric renal transplant recipients and is therefore a useful tool for the optimization of CsA therapy.
Gesehen am 02.02.2023